Trends of fetal chromosome analysis by amniocentesis before and after beginning of noninvasive prenatal testing: A single‐center experience in Japan. Issue 11 (10th August 2021) - Goto, Shinobu; Suzumori, Nobuhiro; Kumagai, Kyoko; Otani, Ayano; Ogawa, Shino; Sawada, Yuki; Inuzuka, Saki; Sugiura‐Ogasawara, Mayumi
Abstract: Aim: This study is to investigate the role of amniocentesis for prenatal diagnosis before and after the beginning of noninvasive prenatal testing (NIPT) in Japan. Methods: We performed a retrospective analysis of genetic amniocentesis at mid‐trimester (15–20 gestational weeks) for fetal karyotype analysis at Nagoya City University between April 2006 and March 2020. The indications, test results, and the detection rate of fetal abnormal karyotype were compared before (phase 1, P1) and after (phase 2, P2) beginning of NIPT at April 2013. Results: A total of 2458 (P1: 1132, P2: 1326) amniocentesis were enrolled in this study. The most frequent indication was advanced maternal age in both phases (P1: 78.2% %, P2: 81.1%). In P2, 110 patients (8.3%) received amniocentesis after positive or nonreportable NIPT results. Other indications were fetal abnormal findings by ultrasounds (P1: 15.4%, P2: 17.7%), abnormal maternal serum screening results (P1: 8.0%, P2: 10%), previous child with fetal chromosome aberration (P1: 6.5%, P2: 3.5%), and translocation of either partner (P1:1.5%, P2: 2.1%). The detection rate for fetal chromosomal aberrations including all indications was significantly increased in P2 (15.9%, 95% CI 14.0–18.0) as compared to P1 (9.0%, 7.4–10.8). However, if the indication was only advanced maternal age, the positive detection rate kept low in both phases (P1: 5.2%, 3.7–7.1, P2: 4.2%, 2.9–5.9). Conclusion: Since the initiation of NIPT, the detection rate of fetal chromosomal abnormalities was higher in this study, suggesting that amniocentesis cannot be strongly recommended for advanced maternal age alone.